Comparative Analysis of P450 Signature Motifs EXXR and CXG in the Large and Diverse Kingdom of Fungi: Identification of Evolutionarily Conserved Amino Acid Patterns Characteristic of P450 Family - Syed, Khajamohiddin; Mashele, Samson Sitheni (PLOS ONE, 2014)
Cytochrome P450 monooxygenases (P450s) are heme-thiolate proteins distributed across the biological kingdoms. P450s are catalytically versatile and play key roles in organisms primary and secondary metabolism. Identification of P450s across the biological kingdoms depends largely on the identification of two P450 signature motifs, EXXR and CXG, in the protein sequence. Once a putative protein has been identified as P450, it will be assigned to a family and subfamily based on the criteria that P450s within a family share more than 40% homology and members of subfamilies share more than 55% homology. However, to date, no evidence has been presented that can distinguish members of a P450 family. Here, for the first time we report the identification of EXXR- and CXG-motifs-based amino acid patterns that are characteristic of the P450 family. Analysis of P450 signature motifs in the under-explored fungal P450s from four different phyla, ascomycota, basidiomycota, zygomycota and chytridiomycota, indicated that the EXXR motif is highly variable and the CXG motif is somewhat variable. The amino acids threonine and leucine are preferred as second and third amino acids in the EXXR motif and proline and glycine are preferred as second and third amino acids in the CXG motif in fungal P450s. Analysis of 67 P450 families from biological kingdoms such as plants, animals, bacteria and fungi showed conservation of a set of amino acid patterns characteristic of a particular P450 family in EXXR and CXG motifs. This suggests that during the divergence of P450 families from a common ancestor these amino acids patterns evolve and are retained in each P450 family as a signature of that family. The role of amino acid patterns characteristic of a P450 family in the structural and/or functional aspects of members of the P450 family is a topic for future research.